Extracción de polifenoles presentes en la cáscara de papa mediante el método de extracción Soxhlet a nivel de laboratorio (2022)
In recent years, potato consumption has been on the rise, becoming one of the most important crops worldwide. Likewise, the generation of residues produced by this tuber is worrying due to the little management that is imposed on them. This research delves into the reuse that can be given to the potato skin, with the main objective being the extraction of compounds with antioxidant activity that are part of this residue, the polyphenols.